Engineering of high-performance potassium-ion capacitors using polyaniline-derived N-doped carbon nanotubes anode and laser scribed graphene oxide cathode. (September 2019) - Moussa, Mahmoud; Al-Bataineh, Sameer A.; Losic, Dusan; Dubal, Deepak P.
Graphical abstract: We have demonstrated a high performance potassium ion hybrid capacitor (KIHC) using nitrogen doped carbon nanotubes (N-CNTs) anode and 3D porous laser scribed graphene (LSG) cathode. Highlights: Engineering of N-doped carbon nanotubes anode and laser scribed graphene oxide cathode for potassium ion battery. Development of all nanocarbon potassium ion capacitor. High energy and high power energy storage system. Abstract: Potassium (K) ion storage technology is recently receiving a great attention due to their low-cost and enormous abundance on the earth compared to lithium. However, the technology is still at a scientific research stage and exploring suitable electrode materials is a key challenge. Herein, we have engineered nitrogen doped carbon nanotubes (N-CNTs) as a promising anode material for K-ion storage through pyrolytic decomposition of polyaniline nanotubes (PAni-NTs). These N-CNTs delivers high reversible capacity with good rate performance and cycling stability. Taking advantage of these features, a potassium-ion hybrid capacitor (KIHC) is constructed using N-CNTs as battery-type anode and 3-dimensional (3D) laser scribed graphene (LSG) as capacitor-type cathode electrodes. The device displays a high energy density of 65 W h/kg, a high power output of 1000 W/kg, as well as a long cycling life (91% capacity retention over 5000 cycles). Thus, such an advanced energy storage system can satisfy the requirements of high power and high energy densities simultaneously in diverse applications at low-cost.